INVESTIGATION OF MARKETING TECHNOLOGIES IN THE INNOVATION PROCESS OF ROCKET AND SPACE INDUSTRY - K. B. Dobrova (Модернизация, инновация, развитие)
In this article we have studied the use of marketing technologies in the innovation process of enterprises of rocket and space industry. The present study specifies the relevance of chosen research topic, as well as the essence of marketing innovations at the enterprises of rocket and space industry, the structuring of marketing and management processes in the innovation process. There are provided the most common analytical instruments in the marketing and there is marked the importance of use of a global strategy for the enterprises of rocket and space industry. The article also specifies a clear example of application of marketing technologies in the innovation process of the Federal State Unitary Enterprise "State Space Research and Production Center named after Khrunichev M.V'.'. At the beginning the role and place of innovation management and innovation process in the strategic management of the FSUE "SSRPC named after Khrunichev M.V." are shown. Then there are described the basic marketing methods of program-oriented management of the innovation process in the FSUE "SSRPC named after Khrunichev M.V"" and there is highlighted the innovation marketing strategy of the FSUE "SSRPC named after Khrunichev M.V.". There are presented the distinctive features of the competitive strategy of the company of the rocket and space industry and the features of formation (development) of the innovative enterprise development strategy based on marketing innovation in the FSUE "SSRPC named after Khrunichev M.V.". The conclusion includes the main findings of the study conducted.